Challenges and Possibilities of Educational Equity and Equality in the Post-COVID-19 Realm in the Nordic Countries - Metsämuuronen Jari; Lehikko Anu (Routledge, Taylor & Francis Group, 2022)
The aim of the article is to offer a base for discussions on educational equality from the viewpoint of changes in the world causing widening disparities between pupils and students. The essence and possibilities of educational equity and equality in the Nordic educational realm are discussed from six viewpoints. The outcome is that all children have the moral right to access equal opportunities even though they are different and unique. Second, we cannot find absolute equality between individuals because all individuals are different and unique. Third, we should find political and pedagogical ways in which to handle educational inequalities. Fourth, students who are not motivated and skilled to undertake independent work may be in danger of being left behind. Fifth, the COVID-19 pandemic has exacerbated the differences between students and diminished the possibilities of students who are vulnerable. Finally, new technologies may open new paths to reduce educational inequality.